Aiming at Good Work: The Conference of European Churches in the Face of the Global Changes in the Area of Work - Kopiec, Piotr (Ecumeny and law, 2024)
The future of human work is one of the crucial issues the ecumenical movement reflects on. For example, the question plays an essential role in the social teaching of theConference of European Churches. Apart from issuing many documents and statements, the organisation established the Church Action on Labour and Life (CALL), a working group called to promote a Christian viewpoint in European and global discussions about a just socio-economic order, including employment and labour. The article outlines the teaching on human work developed by the CALL, setting it in the broader context of the current debate on the future of work. It also briefly considers similarities between the CALL’s concepts and the approaches of Churches in Europe, with emphasis on the Evangelical Church in Germany. Finally, the article discusses the concept of good work and the guidelines for sustainable digitisation, which are CALL’s primary area of focus and its biggest achievement.